Bony cystic lesion with associated submandibular lymphadenopathy on a background of breast carcinoma: an unexpected case of cervicofacial actinomycosis. Issue 4 (6th April 2020) - Sibanda, Lwazi; Wates, Emma; Higginson, James
Abstract : Actinomycosis is an uncommon, chronic suppurative granulomatous infection and needs to be considered as a differential diagnosis. A 56-year-old woman with a background of type 2 diabetes mellitus and breast carcinoma was referred to the Oral and Maxillofacial Surgery 2-week wait clinic, regarding a tender sublingual mass and firm erythematous swelling in the right submandibular and submental region. This was slowly progressive and had not responded to oral co-amoxiclav. An orthopantomogram showed a well-defined radiolucency and smaller radiolucent lesions throughout the edentulous right body of the mandible. A contrast-enhanced CT confirmed a right submandibular abscess communicating with cavitating lesions. The differentials included osteomyelitis, bony metastases, multiple myeloma or other cystic lesions. The patient underwent incision and drainage of the abscess, alongside biopsies, and intravenous co-amoxiclav was given. Microbiology cultures confirmed the presence of Actinomyces israelii and a diagnosis of cervicofacial actinomycosis with mandibular osteomyelitis. The patient was successfully treated with prolonged antibiotics.